Method for improving tensile strength of lithium battery copper foil

By introducing PB2+ions and other additives in the electrolytic solution of lithium batteries and copper foil, optimizing the micro -structure and surface alloying of copper foil, solving the problem of insufficient lithium copper foil tensile strength, significantly increased its tensile strength and extension rate. Meet the performance and safety requirements of lithium ion batteries.

CN119372723APending Publication Date: 2025-01-28HUBEI NORD COPPER FOIL NEW MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411510750.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The tensile strength of the existing lithium-ion copper foil cannot meet the performance and safety requirements of lithium-ion batteries, especially in terms of the mechanical stability, energy density, cycle life and production efficiency of the battery.

Method used

By introducing specific additives in the electrolyte, especially PB2+ions, combined with appropriate electrolyte concentration and temperature control, the micro -structure and surface alloy of copper foil are optimized, thereby significantly enhance the tensile strength and extension rate of copper foil.

Benefits of technology

The tensile strength of lithium battery and copper foil has been significantly improved, and the extension rate remains good. The mechanical performance and surface quality of copper foil reaches excellent levels, and the performance and safety requirements of lithium ion battery are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372723A_ABST
    Figure CN119372723A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the tensile strength of a lithium battery copper foil, and belongs to the technical field of electrolytic copper foil processing. The method comprises the following steps: S1, generating an electrolyte in a copper dissolving tank, and enabling a copper wire and sulfuric acid to generate a copper sulfate electrolyte under the action of a Roots blower and water vapor; s2, the electrolyte in the copper dissolving tank and a small amount of crude foil engine reflux liquid are stored in a liquid storage tank, meanwhile, sulfuric acid needed by reaction is added into the tank, and the concentration and the temperature of the electrolyte are regulated and controlled to be close to those needed by the reaction; s3, the electrolyte flows into a clean liquid tank after passing through a filter; s4, the electrolyte enters the high-level tank, the redundant electrolyte flows back to the clean liquid tank, and an additive needs to be added into the high-level tank; and S5, the electrolyte enters a foil generating machine for electrolytic foil generating. The specific additive is introduced into the electrolyte, so that the tensile strength and the elongation of the copper foil are remarkably improved, the double-sided roughness of the copper foil is effectively controlled, and the mechanical property and the surface quality of the copper foil are ensured to reach an excellent level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field related to electrolytic copper foil processing, and specifically to a method for improving the tensile strength of lithium battery copper foil. Background Art

[0002] In the production of lithium-ion batteries, electrolytic copper foil is the core material of the negative electrode current collector, and its tensile strength has a direct impact on the performance of the battery. With the development of new energy vehicles and energy storage, higher requirements are placed on the energy density and safety of lithium batteries. Tensile strength is one of the important physical performance indicators of lithium battery copper foil, which directly affects the safety and energy density of the battery. The following is the specific impact of tensile strength on the energy density and safety of lithium batteries:

[0003] 1. Improve the mechanical stability of the battery: Copper foil is used as the negative electrode current collector of lithium-ion batteries. Its high tensile strength means that during the battery charging and discharging process, especially when the battery expands or contracts, the copper foil can better withstand mechanical stress and reduce the risk of rupture, thereby improving the safety of the battery.

[0004] 2. Improve battery energy density: Copper foil with high tensile strength can be made thinner, thereby reducing the weight and volume of the battery, which helps to improve the battery energy density. Battery companies are increasingly requiring the tensile strength of lithium battery copper foil to meet the needs of increasing battery energy density.

[0005] 3. Improve the cycle life of the battery: Copper foil with high tensile strength can maintain structural stability during multiple charge and discharge cycles of the battery, reduce the occurrence of cracks and fractures, and thus extend the service life of the battery.

[0006] 4. Improve production efficiency: Copper foil with high tensile strength and high elongation can improve the coating and rolling efficiency in battery production, avoid belt breakage, and improve production efficiency.

[0007] 5. Reduce electrode thickness: High mechanical properties can withstand higher compaction force, enhance the compaction density of the electrode sheet and reduce the thickness of the electrode sheet, further reduce the weight of the battery and increase the energy density of the battery.

[0008] 6. Improve battery durability: Copper foil with high tensile strength can better inhibit the deformation of active materials during battery cycling, thereby improving battery durability and service life.

[0009] 7. Safety design: In the design of lithium batteries, high tensile strength copper foil can be used as part of the safety design to prevent internal short circuit or thermal runaway events caused by mechanical stress during battery use.

[0010] In summary, the tensile strength of copper foil is a key factor in ensuring the performance and safety of lithium batteries. After the existing lithium battery copper foil is processed with the electrolyte, its tensile strength cannot meet the above requirements. Therefore, a method for improving the tensile strength of lithium battery copper foil is proposed to solve the above problem. Summary of the invention

[0011] The object of the present invention is to provide a method for improving the tensile strength of lithium battery copper foil to solve the above-mentioned problem.

[0012] To achieve the above object, the present invention provides the following technical solution: A method for improving the tensile strength of lithium battery copper foil, characterized in that it comprises the following steps:

[0013] S1: Generate electrolyte in the copper dissolving tank, and make copper wire and sulfuric acid generate copper sulfate electrolyte under the action of Roots blower and water vapor:

[0014] Copper wire: diameter 3mm,

[0015] Sulfuric acid: purity 98%,

[0016] Roots blower: provides compressed air, which is the oxygen required for the reaction.

[0017] Steam: Provides a high temperature environment, 70-90°C,

[0018] The copper dissolving tank controls the content of the electrolyte by the amount of reaction and the reaction temperature in the tank. The concentration and temperature of the generated electrolyte are:

[0019] Copper ion: 100-150g / L,

[0020] Acid ions: 50-80g / L,

[0021] Electrolyte temperature: 60-70°C;

[0022] S2: The electrolyte in the copper dissolving tank and a small amount of reflux liquid from the foil production machine are stored in the liquid storage tank. At the same time, the sulfuric acid required for the reaction is also added to this tank, and the concentration and temperature of the electrolyte are adjusted to be close to the reaction requirements. The acid concentration of the electrolyte decreases after circulation in the liquid storage tank and the copper dissolving tank, and the high concentration of acid refluxed from the foil production machine further maintains the required acid concentration to ensure that the foil production conditions are met:

[0023] Copper ion: 90-100g / L,

[0024] Acid ions: 80-90g / L,

[0025] Electrolyte temperature: 48-52°C;

[0026] S3: The electrolyte flows into the clean liquid tank after passing through the filter. In order to maintain the continuous stability of the process, the liquid level of the clean liquid tank is controlled within a certain range:

[0027] S4: The electrolyte enters the high-level tank. The electrolyte entering the foil machine needs to have a stable flow rate or flow. The flow rate is mainly determined by the potential energy difference between the high-level tank and the electrolytic cell. It can also be adjusted by the rotor flowmeter. The liquid level of the electrolyte in the high-level tank is always kept constant, and the excess electrolyte flows back to the clean liquid tank. Additives need to be added to the high-level tank:

[0028] Copper ion: 90-100g / L,

[0029] Acid ions: 80-90g / L,

[0030] Electrolyte temperature: 48-52°C,

[0031] Additives: Agent A+Agent B+Agent C;

[0032] S5: The electrolyte enters the foil production machine for electrolytic foil production.

[0033] As a preferred technical solution of the present invention, the additive in step S4 is a special metal ion additive.

[0034] As a preferred technical solution of the present invention, the electrolyte in step S4 includes copper ions, sulfuric acid, chloride ions and mixed additives, and the mixed additives include agent A, agent B and agent C.

[0035] As a preferred technical solution of the present invention, the copper ion concentration is 90-100 g / L, the sulfuric acid concentration is 100-120 g / L, and the chloride ion concentration is 10-30 ppm.

[0036] As a preferred technical solution of the present invention, the electrolyte temperature is 48-52°C.

[0037] As a preferred technical solution of the present invention, the A agent is one of collagen, gelatin or HEC, with a content of 10-50ppm, and the B agent is one of polydisulfide propane sulfonate sodium (SPS) or 3-sulfur-isothiourea propyl sulfonic acid (UPS) or N or N-dimethyldithiocarboxamide propane sulfonate sodium (DPS), with a content of 1-5ppm.

[0038] As a preferred technical solution of the present invention, the C agent is one of lead chloride or lead dioxide, and the content of the C agent is less than 5ppm.

[0039] As a preferred technical solution of the present invention, the purity of the lead chloride or lead dioxide is required to be greater than 99%.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] In the process of electrolytic copper deposition, the present invention introduces specific additives into the electrolyte to achieve a significant improvement in the tensile strength and elongation of the copper foil, and effectively controls the double-sided roughness of the copper foil, ensuring that the mechanical properties and surface quality of the copper foil reach excellent levels.

[0042] The additives include not only traditional organic substances, but also specific metal ions. These metal ions interact with the copper ions in the electrolyte, promote the alloying of the copper foil surface or the optimization of the microstructure, and thus enhance the mechanical properties of the copper foil. In particular, the present invention introduces Pb into the electrolyte. 2+ This innovative move has enabled the tensile strength of 4.5um lithium battery copper foil to reach 41.6MPa and the elongation to remain at 9.1%. 2+ The mechanism of action of the ions is their deposition in the copper grain boundaries, which effectively hinders the grain boundary sliding of the copper foil during the stretching process, thus giving the copper foil excellent tensile properties. 2+ During the electrolysis process, the ions are deposited on the coating of the anode plate and converted into PbO2 under power-on conditions. This conversion process forms a stable oxide film that effectively prevents the IrO2 coating from peeling off from the titanium substrate, thereby significantly improving the service life of the anode plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a metallographic image of a cross section of a sample of Example 8 of the present invention;

[0044] Figure 2 This is a metallographic diagram of a cross section of a sample of Comparative Example 1 of the present invention;

[0045] Figure 3 This is a metallographic diagram of the cross section of the sample of Example 8 of the present invention - color diagram;

[0046] Figure 4 This is a color metallographic image of the cross section of the sample of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The present invention provides a technical solution comprising the following steps:

[0049] S1: generating electrolyte in the copper dissolving tank, making copper wire and sulfuric acid generate copper sulfate electrolyte under the action of Roots blower and water vapor: copper wire: diameter 3mm, sulfuric acid: purity 98%, Roots blower: providing compressed air, i.e. oxygen required for reaction, water vapor: providing high temperature environment, temperature 70-90℃, copper dissolving tank controls the content of electrolyte by the amount of reaction and reaction temperature in the tank, the generated electrolyte concentration and temperature: copper ion: 100-150g / L, acid ion: 50-80g / L, electrolyte temperature: 60-70℃;

[0050] S2: The electrolyte in the copper dissolving tank and a small amount of reflux liquid from the foil production machine are stored in the liquid storage tank. At the same time, sulfuric acid required for the reaction is also added to this tank, and the concentration and temperature of the electrolyte are adjusted to be close to the reaction requirements. The acid concentration of the electrolyte is reduced after circulation in the liquid storage tank and the copper dissolving tank, and the high concentration of acid refluxed from the foil production machine further maintains the required acid concentration to ensure that the foil production conditions are met: copper ion: 90-100g / L, acid ion: 80-90g / L, electrolyte temperature: 48-52℃;

[0051] S3: The electrolyte flows into the clean liquid tank after passing through the filter. In order to maintain the continuous stability of the process, the liquid level of the clean liquid tank is controlled within a certain range:

[0052] S4: The electrolyte enters the high-level tank. The electrolyte entering the foil machine needs to have a stable flow rate or flow. The flow rate is mainly determined by the potential energy difference between the high-level tank and the electrolytic cell. It can also be adjusted by the rotor flowmeter. The liquid level of the electrolyte in the high-level tank is always kept constant, and the excess electrolyte flows back to the clean liquid tank. Additives need to be added to the high-level tank: copper ions: 90-100g / L, acid ions: 80-90g / L, electrolyte temperature: 48-52℃, additives: A agent + B agent + C agent;

[0053] S5: The electrolyte enters the foil production machine for electrolytic foil production.

[0054] The additive is a special metal ion additive, the temperature of the electrolyte is 48-52° C., the electrolyte includes copper ions with a copper ion concentration of 90-100 g / L, sulfuric acid with a sulfuric acid concentration of 100-120 g / L, chloride ions with a chloride ion concentration of 10-30 ppm, and mixed additives, wherein the mixed additives include agent A, agent B, and agent C, agent A is one of collagen, gelatin, or HEC, with a content of 10-50 ppm, agent B is one of polydisulfide propane sulfonate sodium (SPS), 3-sulfur-isothiourea propyl sulfonic acid (UPS), or N or N-dimethyldithiocarboxamide propane sulfonate sodium (DPS), with a content of 1-5 ppm, agent C is one of lead chloride or lead dioxide, the content of agent C is less than 5 ppm, and the purity of lead chloride or lead dioxide is required to be greater than 99%.

[0055] In the process of electrolytic copper deposition, the present invention introduces specific additives into the electrolyte to achieve a significant improvement in the tensile strength and elongation of the copper foil, and effectively controls the double-sided roughness of the copper foil, ensuring that the mechanical properties and surface quality of the copper foil reach excellent levels.

[0056] The additives include not only traditional organic substances, but also specific metal ions. These metal ions interact with the copper ions in the electrolyte, promote the alloying of the copper foil surface or the optimization of the microstructure, and thus enhance the mechanical properties of the copper foil. In particular, the present invention introduces Pb into the electrolyte. 2+ This innovative move has enabled the tensile strength of 4.5um lithium battery copper foil to reach 41.6MPa and the elongation to remain at 9.1%. 2+ The mechanism of action of the ions is their deposition in the copper grain boundaries, which effectively hinders the grain boundary sliding of the copper foil during the stretching process, thus giving the copper foil excellent tensile properties. 2+ During the electrolysis process, the ions are deposited on the coating of the anode plate and converted into PbO2 under power-on conditions. This conversion process forms a stable oxide film that effectively prevents the IrO2 coating from peeling off from the titanium substrate, thereby significantly improving the service life of the anode plate.

[0057] Example 1

[0058] The present invention provides an electrolyte for improving the tensile strength of lithium battery copper foil and a preparation method thereof. The specific test conditions of the high-level tank are as follows:

[0059] Copper ion: 90-100g / L

[0060] Acid ion: 80-90g / L

[0061] Electrolyte temperature: 48-52℃.

[0062] Additive A: Collagen 10ppm

[0063] Additive B: DPS 1ppm

[0064] Additive C: Lead chloride 0.5ppm

[0065] Example 2

[0066] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0067] Additive A: Collagen 50ppm

[0068] Additive B: DPS 1ppm

[0069] Additive C: Lead chloride 0.5ppm

[0070] Example 3

[0071] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0072] Additive A: Collagen 10ppm

[0073] Additive B: DPS 5ppm

[0074] Additive C: Lead chloride 0.5ppm

[0075] Example 4

[0076] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0077] Additive A: Collagen 50ppm

[0078] Additive B: DPS 5ppm

[0079] Additive C: Lead chloride 0.5ppm

[0080] Example 5

[0081] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0082] Additive A: Collagen 10ppm

[0083] Additive B: DPS 1ppm

[0084] Additive C: Lead chloride 4ppm

[0085] Example 6

[0086] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0087] Additive A: Collagen 50ppm

[0088] Additive B: DPS 1ppm

[0089] Additive C: Lead chloride 4ppm

[0090] Example 7

[0091] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0092] Additive A: Collagen 10ppm

[0093] Additive B: DPS 5ppm

[0094] Additive C: Lead chloride 4ppm

[0095] Example 8

[0096] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0097] Additive A: Collagen 50ppm

[0098] Additive B: DPS 5ppm

[0099] Additive C: Lead chloride 4ppm

[0100] Example 9

[0101] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0102] Additive A: Collagen 10ppm

[0103] Additive B: DPS 1ppm

[0104] Additive C: Lead chloride 6ppm

[0105] Example 10

[0106] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0107] Additive A: Collagen 50ppm

[0108] Additive B: DPS 1ppm

[0109] Additive C: Lead chloride 6ppm

[0110] Embodiment 11

[0111] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0112] Additive A: Collagen 10ppm

[0113] Additive B: DPS 5ppm

[0114] Additive C: Lead chloride 6ppm

[0115] Example 12

[0116] The difference between this embodiment and embodiment 1 is that the concentration of additives is different, and the specific situation is as follows:

[0117] Additive A: Collagen 50ppm

[0118] Additive B: DPS 5ppm

[0119] Additive C: Lead chloride 6ppm

[0120] Comparative Example 1

[0121] The difference between this comparative example and the example is that the additive component does not include agent C, and the concentrations of other components are consistent with Example 8 because it has the best effect.

[0122] Additive A: Collagen 50ppm

[0123] Additive B: DPS 5ppm

[0124] The following table is the full factorial DOE design table of the embodiment (Table 1):

[0125] Table 1 Example full factorial DOE design table

[0126] Standard sequence Agent A / ppm Agent B / ppm Agent C / ppm Example 1 10 1 0.5 Example 2 50 1 0.5 Example 3 10 5 0.5 Example 4 50 5 0.5 Example 5 10 1 4 Example 6 50 1 4 Example 7 10 5 4 Example 8 50 5 4 Example 9 10 1 6 Example 10 50 1 6 Embodiment 11 10 5 6 Example 12 50 5 6 Comparative Example 1 50 5 0

[0127] The relevant equipment and test methods are as follows:

[0128] Metallographic analysis: Using the 3D ultra-depth microscope VHX-X1F provided by Keyence;

[0129] Tensile strength and elongation test: According to the test method GB / T29847-2013, the tensile strength and elongation of the copper foil were tested at room temperature (about 25°C) using an AGS-X series universal material testing machine manufactured by SHIMADZU.

[0130] The basic physical property test results of the electrolytic copper foils prepared in Examples 1-12 and Comparative Example 1 are shown in the following table (Table 2):

[0131] Table 2 Physical properties test results of electrolytic copper foil

[0132] Case Thickness / um High temperature tensile strength / MPa High temperature elongation / % Example 1 4.5 32.8 8.8 Example 2 4.5 34.2 9.7 Example 3 4.5 32.4 9.6 Example 4 4.5 37.5 9.8 Example 5 4.5 34.6 9.1 Example 6 4.5 36.6 8.9 Example 7 4.5 35.8 9.5 Example 8 4.5 41.6 9.1 Example 9 4.5 35.8 7.8 Example 10 4.5 36.6 6.9 Embodiment 11 4.5 34.4 6.1 Example 12 4.5 37.3 7.5 Comparative Example 1 4.5 36.6 9.6

[0133] Table 2 shows the physical properties of the electrolytic copper foil prepared according to the technical process provided by the present invention. The tensile strength of the sample prepared in Example 8 reaches 41.6MPa, and the elongation also maintains a good level of 9.1%. It is worth noting that Examples 9-12 are samples prepared under a higher level of PD2+ content, and their elongation is significantly lower than that of other embodiments. This is because when the PD2+ content is too high, it is stored in the copper grain boundary in the form of impurities, thereby sharply reducing the elongation. In addition, it can be clearly seen from the table that in Comparative Example 1, the sample prepared by the electrolyte without adding PD2+ has the lowest tensile strength, which further proves the excellence of the present invention.

[0134] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for improving the tensile strength of lithium battery copper foil, characterized in that: The following steps are involved: S1: Generate electrolyte in the copper dissolving tank, and make copper wire and sulfuric acid generate copper sulfate electrolyte under the action of Roots blower and water vapor: Copper wire: diameter 3mm, Sulfuric acid: purity 98%, Roots blower: provides compressed air, which is the oxygen required for the reaction. Steam: Provides a high temperature environment, 70-90°C, The copper dissolving tank controls the content of the electrolyte by the amount of reaction and the reaction temperature in the tank. The concentration and temperature of the generated electrolyte are: Copper ion: 100-150g / L, Acid ions: 50-80g / L, Electrolyte temperature: 60-70°C; S2: The electrolyte in the copper dissolving tank and a small amount of reflux liquid from the foil production machine are stored in the liquid storage tank. At the same time, the sulfuric acid required for the reaction is also added to this tank, and the concentration and temperature of the electrolyte are adjusted to be close to the reaction requirements. The acid concentration of the electrolyte decreases after circulation in the liquid storage tank and the copper dissolving tank, and the high concentration of acid refluxed from the foil production machine further maintains the required acid concentration to ensure that the foil production conditions are met: Copper ion: 90-100g / L, Acid ions: 80-90g / L, Electrolyte temperature: 48-52°C; S3: The electrolyte flows into the clean liquid tank after passing through the filter. In order to maintain the continuous stability of the process, the liquid level of the clean liquid tank is controlled within a certain range: S4: The electrolyte enters the high-level tank. The electrolyte entering the foil machine needs to have a stable flow rate or flow. The flow rate is mainly determined by the potential energy difference between the high-level tank and the electrolytic cell. It can also be adjusted by the rotor flowmeter. The liquid level of the electrolyte in the high-level tank is always kept constant, and the excess electrolyte flows back to the clean liquid tank. Additives need to be added to the high-level tank: Copper ion: 90-100g / L, Acid ions: 80-90g / L, Electrolyte temperature: 48-52°C, Additives: Agent A+Agent B+Agent C; S5: The electrolyte enters the foil production machine for electrolytic foil production.

2. A method for improving the tensile strength of lithium battery copper foil according to claim 1, characterized in that: The additive in step S4 is a special metal ion additive.

3. The method for improving the tensile strength of lithium battery copper foil according to claim 1, characterized in that: The electrolyte in step S4 includes copper ions, sulfuric acid, chloride ions and mixed additives, and the mixed additives include agent A, agent B and agent C.

4. A method for improving the tensile strength of lithium battery copper foil according to claim 3, characterized in that: The copper ion concentration is 90-100 g / L, the sulfuric acid concentration is 100-120 g / L, and the chloride ion concentration is 10-30 ppm.

5. The method for improving the tensile strength of lithium battery copper foil according to claim 3, characterized in that: The electrolyte temperature is 48-52°C.

6. A method for improving the tensile strength of lithium battery copper foil according to claim 3, characterized in that: The agent A is one of collagen, gelatin or HEC, with a content of 10-50ppm, and the agent B is one of polydisulfide propane sulfonate sodium (SPS) or 3-thio-isothiourea propyl sulfonic acid (UPS) or N or N-dimethyldithiocarboxamide propane sulfonate sodium (DPS), with a content of 1-5ppm.

7. The method for improving the tensile strength of lithium battery copper foil according to claim 3, characterized in that: The C agent is one of lead chloride or lead dioxide, and the content of the C agent is less than 5ppm.

8. The method for improving the tensile strength of lithium battery copper foil according to claim 7, characterized in that: The purity of the lead chloride or lead dioxide is required to be greater than 99%.